The Relationship of Mental Health with Learning Achievement in Adolescent - Mukarom, Muhammad Zulfikri; Daeli, Weslei (Cities and Urban Development Journal, 2023)
Background: Mental health is not yet considered important in some countries. The most common mental health disorder in teenagers is depression. This research aims to determine whether there is a relationship between mental health and academic achievement in adolescents. When mental disorders occur, there will be problems with attention and concentration, health problems, difficulty understanding the material and motivation to learn will also decrease, affecting grades or achievement at school. Aims: This research aims to determine whether there is a relationship between mental health and academic achievement in adolescents. Methods: The mental health measuring tool uses SRQ-29 (Self reporting Questionnaire 29) which is standard from WHO. The number of respondents was 73 respondents at SMK X Bogor. The method used is correlation description. Results: Based on research results, the frequency distribution of respondents based on learning achievement shows that the majority of teenagers have completed their grades. Conclusion: There is a relationship between mental health and learning achievement. Then teachers understand more about the development of adolescent characteristics so that students feel comfortable when conducting counseling and schools need to provide facilities for students to develop their talents positively.